2019
DOI: 10.1242/dmm.037994
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in GNB5 causes bradycardia by augmenting the cholinergic response via increased acetylcholine-activated potassium current (IK,ACh)

Abstract: Mutations in GNB5 , encoding the G-protein β5 subunit (Gβ5), have recently been linked to a multisystem disorder that includes severe bradycardia. Here, we investigated the mechanism underlying bradycardia caused by the recessive p.S81L Gβ5 variant. Using CRISPR/Cas9-based targeting, we generated an isogenic series of human induced pluripotent stem cell (hiPSC) lines that were either wild type, heterozygous or homozygous for the GNB5 p.S81L variant. These were diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 48 publications
7
15
0
Order By: Relevance
“…Overall, the APs of our atrial-like hiPSC-CMs were substantially shorter and had a lower AP plateau than those of our ventricular-like hiPSC-CMs, in qualitative agreement with previous studies on atrial- and ventricular-like hiPSC-CMs ( Marczenke et al, 2017 ; Verkerk et al, 2017 ; Argenziano et al, 2018 ; Cyganek et al, 2018 ; Lemme et al, 2018 ; Veerman et al, 2019 ). There are some quantitative differences in AP parameters with previous studies, but these are likely due to differences in cell lines, differences in differentiation protocols, absence or presence of I K 1 injection, and a different definition of AP plateau amplitude.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the APs of our atrial-like hiPSC-CMs were substantially shorter and had a lower AP plateau than those of our ventricular-like hiPSC-CMs, in qualitative agreement with previous studies on atrial- and ventricular-like hiPSC-CMs ( Marczenke et al, 2017 ; Verkerk et al, 2017 ; Argenziano et al, 2018 ; Cyganek et al, 2018 ; Lemme et al, 2018 ; Veerman et al, 2019 ). There are some quantitative differences in AP parameters with previous studies, but these are likely due to differences in cell lines, differences in differentiation protocols, absence or presence of I K 1 injection, and a different definition of AP plateau amplitude.…”
Section: Discussionsupporting
confidence: 92%
“…Among the GNB5 pathogenic variants described so far [66,[120][121][122][123][124][125], a mutational hot spot in exon 2, encoding the first WD40 domain and containing 58% of described variants, has been identified ( Figure 2). The evidence of the GNB5 involvement in neuronal and cardiac signaling was confirmed in Gnb5-null zebrafish and mouse models that resulted in neuronal and cardiac phenotypes reminiscent of those of IDDCA patients [63,66,126,127].…”
Section: G Protein Subunit Beta (Gnb5 Gβ 5 )mentioning
confidence: 81%
“…Several studies revealed that PKD1 is not only associated with vascular endothelial growth factor (VEGF) 44 but also exhibited differential expression in the myocardial tissue of a rat model 45 . Moreover, TAGAP 46 , AQP4 47,48 , EPHX2 49 and GNB5 50,51 all provided new insights into the molecular mechanisms through the inflammatory response and apoptosis pathways underlying cardiovascular disease regulation. However, this hypothesis should be further investigated.…”
Section: Discussionmentioning
confidence: 99%